2022
DOI: 10.3389/fnagi.2021.751897
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Positron Emission Tomography Tracers for Proteinopathies Imaging in Dementia

Abstract: An early detection and intervention for dementia represent tremendous unmet clinical needs and priorities in society. A shared feature of neurodegenerative diseases causing dementia is the abnormal accumulation and spreading of pathological protein aggregates, which affect the selective vulnerable circuit in a disease-specific pattern. The advancement in positron emission tomography (PET) biomarkers has accelerated the understanding of the disease mechanism and development of therapeutics for Alzheimer’s disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 204 publications
(257 reference statements)
0
10
0
Order By: Relevance
“…To date, in preclinical studies, few probes have been reported to detect α-syn aggregates in vivo using an inoculated mouse model . In this experiment, [ 18 F]­FHCL-2 recognized α-syn aggregates inoculated in the mouse brain, suggesting that 18 F-labeled chalcone analogues might be new ligands for in vivo α-syn imaging.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…To date, in preclinical studies, few probes have been reported to detect α-syn aggregates in vivo using an inoculated mouse model . In this experiment, [ 18 F]­FHCL-2 recognized α-syn aggregates inoculated in the mouse brain, suggesting that 18 F-labeled chalcone analogues might be new ligands for in vivo α-syn imaging.…”
Section: Resultsmentioning
confidence: 86%
“…[ 18 F]­C05-05, known as the C05 series, also depicted α-syn aggregates in vivo in the preclinical stage, and further research, including clinical studies, is expected. Thus, promising probes have been reported; however, no successful in vivo imaging of α-syn aggregates has been reported in the clinical stage, and α-syn-targeted probes are still under development worldwide …”
Section: Introductionmentioning
confidence: 99%
“…Even though more and more tracers were approved by the US Food and Drug Administration and by the European Medicines Agency for clinical usage ( 106 ), the higher cost and longer acquisition times compared to MRI might limit the wide applications in clinical practice ( 107 ). Changes in the levels of human fluid components could reflect underlying pathophysiological processes, and several fluid biomarkers were available or showed potential values such as Aβ, tau, NfL, and progranulin.…”
Section: Discussionmentioning
confidence: 99%
“…The essential neuro-pathological features of AD have been known for almost ~120 years, and currently the presence and abundance of pathological lipoprotein-rich aggregates including amyloid-beta (Aβ) peptide-enriched “senile plaques” (SP) and the accumulation of abnormally hyper-phosphorylated tau (pTau) proteins into twisted neurofilament bundles known as neurofibrillary tangles (NFT) in the AD affected neocortex and hippocampus are still required for an accurate pathological diagnosis of AD at post-mortem examination of the brain (Alzheimer et al, 1995 ; DeTure and Dickson, 2019 ). Recent developments and advancements in RNA sequencing technologies and molecular imaging involving specialized positron emission tomography (PET)-based technologies and the use of multiple biofluid biomarkers have become increasingly useful for assisting in the early diagnosis, prognosis, prediction of time-to-symptom onset and drug treatment-monitoring of complex lipoproteinopathies including AD (Swarbrick et al, 2019 ; Shi et al, 2020 ; Wei et al, 2020 ; Zhao et al, 2020 ; Beach and Malek-Ahmadi, 2021 ; Ni and Nitsch, 2022 ; Ogonowski et al, 2022 ).…”
Section: The Complexity Of Neurodegenerationmentioning
confidence: 99%